Pengaruh Return on Asset, Current Ratio, dan Debt to Equity Ratio Terhadap Harga Saham dengan Firm Size Sebagai Variabel Moderasi (Pada Perusahaan Pertambangan Subsektor Minyak dan Gas Bumi yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2023) - Liana, Natalia; Febriyanti, Diah (Innovative: Journal Of Social Science Research, 2024)
This research aims to determine the effect of Return On Assets (ROA), Current Ratio, Debt to Equity Ratio, on Stock Prices with Firm Size as a moderating variable. The research population of oil and gas subsector growth companies registered on the IDX 2016-2023 is 35 companies. The sampling technique used in this research is the purposive sampling method and based on the technique, the number of samples that meet the requirements is 8 companies with a period of 8 years (2016-2023), the sample is 44 samples. The analytical method used is multiple linear regression analysis. The results of data analysis show that there is a significant influence between Current Ratio and DER, while there is no influence between ROA and Share Prices. The results of the moderation analysis show that ROA and Current Ratio have no moderating effect on share prices, while DER has a moderating effect on share prices. Key words: Return On Asset (ROA), Current Ratio, Debt to Equity Ratio, Stock Prices and Firm Size